IDENTIFICATION OF LEADING SECTORS IN BATU CITY USING LOCATION QUOTIENT, DYNAMIC LOCATION QUOTIENT, AND SHIFT SHARE ANALYSIS - Rama Bhaskara Praja (Jurnal Ekonomi, 2023)
Batu City was ranked 7th for the city/district with the lowest GRDP in East Java. Furthermore, even though it is famous for its tourism, it turned out that the other service sector and the sector providing accommodation and food and drink were not the biggest contributors to GRDP in Batu. Therefore, it is important to find the leading sector in Batu so that it can become the focus of the government in making policies in order to boost the economy. This research was conducted to find leading sectors in Batu using Location Quotient (LQ), Dynamic Location Quotient (DLQ), and Shift-Share. The results of the combined analysis of LQ and DLQ show that there are five leading sectors in Batu City, namely other service sectors; agriculture, forestry and fishery sectors; sector of water supply, waste management, waste and recycling; real estate sector; and the construction sector. Meanwhile, the results of the shift share analysis show only one leading sector, namely the manufacturing sector. From these two results, the Batu Local Government should make policies that prioritize the development of these six leading sectors to be able to boost its economy